Identificação de genótipos de feijoeiro comum resistentes à antracnose por meio de avaliação das reações de incompatibilidade e marcadores moleculares SCAR - Darben, Luana Mieko (2010)
Common bean is one of the most cultivated legumes in the world, standing out as the main source of protein and calories, especially for rural people in Africa and Latin America. As a species grown throughout the year, is constantly vulnerable to attack by pathogenic fungi, among them, the C. lindemuthianum, causal agent of anthracnose, one of the most important common bean diseases, responsible for crop losses up to 100% under ideal conditions of temperature and humidity. C. lindemuthianum is a pathogen that presents a wide genetic variability, providing constant breaks in the resistance of commercial cultivars, requiring researchers to continuous searches for new sources of resistance. In Paraná State, more than 56 races of the pathogen have been identified, and race 73 is one of the most frequent. The objective of the present study was to identify common bean plants resistant to anthracnose through assessment of incompatibility reactions to races 73 and 2047 of C. lindemuthianum associated with the use of molecular markers SCAR SF101072 and SAS13950 linked respectively to the Co-10 gene and allele Co-42. For this, 75 common bean accessions belonging to the Bean Germplasm Bank of Nupagri/UEM were assessed. Based on the results it was possible to identify 30 genotypes resistant to race 73, 36 to race 2047 and 14 genotypes that were resistant to both races. The analysis with SCARs SF101072 and SAS13950 identified 28 and 45 genotypes, respectively, with the presence of the markers. In the joint analysis can be seen that the same markers were efficient, identifying 13 and 21 genotypes resistant to races 73 and 2047, indicating the possible presence of the Co-10 and Co-42 allele, which confers resistance to two races respectively. It was also possible to verify the existence of resistant genotypes without the presence of the marker linked to the gene, which probably indicates the presence of another gene conferring resistance to these races, different to the Co-10 and Co-42, requiring the genetic characterization of these accessions, so that they can be made available for breeding programs. Furthermore, the identification of accessions resistant to C. lindemuthianum by the markers present new perspectives for the use of molecular markers assisted selection, making it more agile and effective selection process in breeding programs.